On Covering Approximation Subspaces - Xun Ge (Computer Science Journal of Moldova, 2009)
Let (U';C') be a subspace of a covering approximation space (U;C) and X⊂U'. In this paper, we show that and B'(X)⊂B(X)∩U'. Also, iff (U;C) has Property Multiplication. Furthermore, some connections between outer (resp. inner) definable subsets in (U;C) and outer (resp. inner) definable subsets in (U';C') are established. These results answer a question on covering approximation subspace posed by J. Li, and are helpful to obtain further applications of Pawlak rough set theory in pattern recognition and artificial intelligence.